Anwar Ibrahim’s Struggle for the Real and Malaysian Politics in Transition - Jared Genser; Sivarasa Rasiah (SIASAT, 2020)
This paper is about Anwar Ibrahim and politics in Malaysia. Anwar Ibrahim was born in a village near Penang, Malaysia on August 10, 1947. His parents were a hospital medical assistant and a housewife who became engaged in local grassroots politics early on. Anwar became involved in politics in 1971 as a pro-Islam student leader, founding the Muslim Youth Movement of Malaysia. He remained its president until 1982.67 Although he was a leader of opposition groups – in fact he was jailed under the Internal Security Act for two years for organizing mass demonstrations in 1974 – Anwar accepted an invitation in 1982 to join the ruling United Malays National Organization (UMNO). Rising quickly through the ranks of the party, he served in succession as the Minister of Culture, Youth, and Sports in 1983, of Agriculture in 1984, of Education from 1986-91, and was appointed Minister of Finance from 1991-98. In 1993, Anwar also became Deputy Prime Minister for Prime Minister Mahathir.68 He served as Deputy Prime Minister until 1998, when he was dismissed, on the pre-text of corruption and sodomy allegations, because of major disagreements with Mahathir about the political and economic direction of Malaysia’s future.